Minimum energy consumption multicast routing in ad hoc networks based on particle swarm optimization - Xiao-jian ZHU; Jun SHEN (Tongxin xuebao)
In wireless ad hoc networks,because devices are powered by batteries,and multicast applications are constantly emerging,how to construct a multicast tree of the minimum energy consumption is an important problem.For the effect of the different choices of relay nodes to the construction of the minimum energy consumption multicast tree,a discrete particle swarm optimization algorithm to optimize the construction of the minimum energy consumption multicast tree was proposed.In order to avoid the premature convergence of the discrete particle swarm optimization algorithm,an inertia weight strategy was introduced to balance the global searchin ability and the local searching ability.The results of simulated experiments show that the modified discrete particle swarm optimization algorithm has strong optimization ability,and can effectively optimize the construction of the minimum energy consumption multicast tree.